A Single Drop Fabrication of the Cholesterol Biosensor Based on Synthesized NiFe2O4NPs Dispersed on PDDA‐CNTs. Issue 12 (13th September 2017) - Moonla, Chochanon; Preechaworapun, Anchana; Tangkuaram, Tanin
Abstract: A cholesterol biosensor based on cholesterol oxidase‐poly(diallyldimethylammonium chloride)‐carbon nanotubes‐nickel ferrite nanoparticles (ChOx‐PDDA‐CNTs‐NiFe2 O4 NPs) solution is easily fabricated by using a single dropping step on a glassy carbon electrode (GCE) surface. This technique is an alternative way to reduce complexity, cost and time to produce the biosensor. The uniformly dispersed materials on the electrode surface enhance the catalytic reaction of cholesterol oxidase and electron transfer from the oxidation of hydrogen peroxide in the system. The nickel ferrite nanoparticles were synthesized by co‐precipitation and calcination at various temperatures. These nanoparticles were then characterized using field emission scanning electron microscopy (FE‐SEM), energy‐dispersive X‐ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FTIR), cyclic voltammetry (CV) and X‐ray diffraction (XRD). The synthesized material calcined at 700 °C was well defined and presented the octahedral metal stretching with cubic NiFe2 O4 NPs phase. In cyclic voltammetric study, the ChOx‐PDDA‐CNTs‐NiFe2 O4 NPs/GCE showed 0.43 s −1 charge transfer rate constant ( K s ), 7.79×10 −6  cm 2  s −1 diffusion coefficient value ( D ), 0.13 mm 2 electroactive surface area ( A e ) and 3.58×10 −8  mol cm −2 surface concentration ( γ ). This modified electrode exhibits stability in term of percent relative standard deviation (%RSD=0.62 %, n=10), reproducibility (%RSD=0.81, n=10), high sensitivity (25.76 nA per mg L −1  cm −2 ), linearity from 1 to 5, 000 mg L −1 (R 2 =0.998) with a low detection limit (0.50 mg L −1 ). Its Michaelis‐Menten constant ( K m ) was 0.14 mM with 0.92 μA maximum current ( I max ) and demonstrated good selectivity without the effects of electroactive species such as ascorbic acid, glucose and uric acid. The cholesterol biosensor was successfully applied to determine cholesterol levels in human blood samples, showing promise due to its simplicity and availability. Abstract :